Phase transition of amorphous cobalt hydroxide to crystalline cobalt oxides by electron-beam irradiation - Minjeong Lee; Hye Seong Jang; Gayoung Yoon; Gyeong Hee Ryu (Applied Microscopy, 2025)
Abstract Transmission electron microscopy (TEM), which can analyze the shape and crystallinity of materials as well as the chemical bonding of ions and the states of elements, operates at different accelerating voltages depending on the type of specimen analyzed and the analysis area. Electron-beam irradiation can be used to induce structural transitions and crystallization of materials. Therefore, studies on phase transition using electron beams have been frequently conducted. Cobalt oxides, including cobalt hydroxides, have various phases and crystal structures, depending on their stoichiometric compositions. Specific synthesis methods can be used to synthesize these at low dimensions, in addition to large nanosheet structures. In this study, the crystallization and phase transition of amorphous cobalt hydroxide nanosheets induced by continuous electron-beam irradiation were analyzed using high-resolution TEM (HR-TEM). The synthesized cobalt hydroxide nanosheets were partially converted into cobalt oxides, and the transferred area expanded as the irradiation time increased. Under 300 kV of accelerating voltage, the transition to cubic cobalt oxides was dominant, suggesting a frequent transitional behavior of amorphous metal hydroxides upon electron-beam irradiation.